Design, Realization and Measurements of Compact Dual-band CPW-fed Patch Antenna for 2.45/5.80 GHz RFID Applications - Mohamed Tarbouch; Abdelkebir El Amri; Hanae Terchoune (Institute of Advanced Engineering and Science, 2018)
In this paper, a Coplanar Wave Guide (CPW)-Fed microstrip octagonal patch antenna for RFID Applications is proposed. The studied structure is suitable for 2.45/5.80 GHz applications. The octagonal shape is obtained by making triangular cuts in the four angles of the rectangular microstrip patch antenna; in addition the using of CPW-Fed allows obtaining UWB characteristics in the higher band. The miniaturization in the antenna size for lower band is achieved by introducing an inverted E slot in the radiating element. The proposed antenna is designed on a single and a small substrate board of dimensions 29.5×29.5×1.6 mm3. Moreover the miniaturized antenna has a good impedance matching and an enhanced gain. The simulation analysis was performed using the CADFEKO software, a Method of Moment (MoM) based solver, and a prototype of this antenna was fabricated, good agreement with the simulation providing validation of the design procedure. The measurements are done with ANRITSU MS2026C Vectorial Network Analyzer.